Penerapan Prinsip Good Governance Dalam Pelayanan Sim Keliling di Polres Bantul - Susilowati, Eni; Supardal, Supardal (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to analyze the implementation of good governance principles in the Mobile Driving License (SIM) service at the Traffic Unit (Satlantas) of Bantul Police. The research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the issuance and renewal services of driving licenses at Satlantas Bantul have been carried out properly and in accordance with the Standard Operating Procedures (SOP). The effectiveness and efficiency aspects of the service are considered optimal, although improvements are still needed in time accuracy and clarity of information delivery to the public. The simplicity of service procedures helps applicants understand the stages of SIM processing, while information transparency is supported through the official social media of Satlantas Bantul. Supporting factors for good service performance include a positive work culture, effective communication, daily motivational briefings, and reward systems for high-performing officers. Meanwhile, inhibiting factors come from limited human resources that are not yet fully professional and a lack of technical training. Overall, the implementation of good governance principles in the Mobile SIM service at Bantul Police has been well executed through improved transparency, accountability, and public service quality.